2001
DOI: 10.1379/1466-1268(2001)006<0238:thfopi>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

&cestflwr;&emsp;The Hsp90 family of proteins in Arabidopsis thaliana

Abstract: The 90-kDa heat shock protein (Hsp90) is an essential molecular chaperone in eukaryotic cells, with key roles in the folding and activation of proteins involved in signal transduction and control of the cell cycle. A search for Hsp90 sequences in the Arabidopsis thaliana genome revealed that this family includes 7 members. The AtHsp90-1 through AtHsp90-4 proteins constitute the cytoplasmic subfamily, whereas the AtHsp90-5, AtHsp90-6, and AtHsp90-7 proteins are predicted to be within the plastidial, mitochondri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
285
0
8

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(301 citation statements)
references
References 50 publications
8
285
0
8
Order By: Relevance
“…CAB78329) was identi®ed by database search in this study. Our search results are in agreement with the ®ndings of Krishna and Gloor (2001). HSP88.1 and HSP89.1 were identi®ed through screening a genomic library using a carrot HSP90 cDNA (Milioni and Hatzopoulos, 1997).…”
Section: Discussionsupporting
confidence: 85%
“…CAB78329) was identi®ed by database search in this study. Our search results are in agreement with the ®ndings of Krishna and Gloor (2001). HSP88.1 and HSP89.1 were identi®ed through screening a genomic library using a carrot HSP90 cDNA (Milioni and Hatzopoulos, 1997).…”
Section: Discussionsupporting
confidence: 85%
“…Silencing of NbHsp90-1 using VIGS vectors carrying fragments of NbHsp90-1 sequence resulted in severe plant developmental defects and ultimately in plant death. In Arabidopsis, there are four Hsp90 homologs (20) that show high homology to NbHsp90-1 (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…1). NbHsp90-1 and -2 possess the C-terminal MEEVD pentapeptide that is characteristic of cytoplasmic Hsp90 proteins (20). Comparison of the amino acid sequences of these proteins with Arabidopsis and human cytoplasmic Hsp90 proteins revealed very high homology (Fig.…”
Section: Identification Of Nbhsp90 As Nbrar1-interacting Partner-mentioning
confidence: 97%
“…16 Two transcripts from our S. iberica analysis closely matched HSP90 (E-value = 1.16 E-116), which is involved in stabilizing cellular proteins upon stress conditions. Koning et al 20 performed a northern blot and a GUS assay of a transgenic Arabidopsis line and showed that HSP80 is upregulated in development.…”
Section: Methodsmentioning
confidence: 71%